Family Vulnerability in Adolescents from Copacabana, Colombia - Paniagua-Suárez, Ramón Eugenio; Gonzalez-Posada, Carlos Mauricio (Advances in Social Sciences Research Journal, 2019)
Objective: to determine which vulnerability-related items from the scale ¿Cómo es tu familia? (How is your Family?) were the most problematic ones in Copacabana (Colombia) during 2010. Methods: a random sample of 406 students aged 11 to 19 was taken. Frequency tables were made to determine the items whose vulnerability values were higher than 40%. Such items were thus classified as problematic (issues). Contingency tables were made with the sex and age group variables. Then, the odds ratio, OR, was found in order to compare vulnerability proportions for each case. The following statistics software was used in this study: SPSS 19.0 and Epiinfo 6.0. Results: there is vulnerability in the following items: communication with the father, family routines, no search for support when the adolescent has problems, poor support provided by the adolescents' families, a great deal of importance placed on having power over others, having money, and having an active sex life. Conclusion: given the severity of the issues in question, they may be considered public health problems.